Egyptian funeral rites and the Fayum masks: from the depths of Earth to eternal life - Petruski, Maura Regina (Romanitas - Revista de Estudos Grecolatinos, 2023)
The funerary traditions of ancient Egypt are intrinsically linked to the belief in an afterlife and the preservation of the body for the journey beyond. Over millennia, the Egyptians developed elaborate funeral rituals and practices to honor the deceased and ensure a successful transition to the afterlife. One of the most notable aspects of these rites is funerary art, which includes the mysterious and fascinating Fayum masks. Discovered in the Fayum region, these masks reveal a unique practice of preservation and devotion to the dead, standing out as artistic expressions and cultural testimonies that transcend time. This article aims to present an analysis of these Egyptian funerary portraits and their production context. We believe that the Fayum masks unveil the complexities of Egyptian funerary rites and represent a significant artifact in the realm of the afterlife. From the perspective of the deceased, these pieces were conceived and designed with an eye toward the future, facilitating a swift journey to the other life—akin to a passport identifying the soul of the individual on the path of their ultimate and most important voyage.